Avaliação da proteção conferida pela vacina antimeningocócica BC no Estado de Santa Catarina, Brazil, 1990/92 Evaluation of the protective efficacy of an antimeningococcal vaccine for serogroups B and C Neisseria meningitidis infections in Brazil, 1990/92 - Eduardo de A. Costa; Horiovaldo Martins; Carlos H. Klein (Universidade de São Paulo, 1996)
São apresentados os resultados da avaliação da vacina antimeningocócica BC de procedência cubana realizada com dados da vigilância epidemiológica de meningites do Estado de Santa Catarina, Brasil, dos anos de 1990-92. A eficácia para os casos confirmados por exames bacteriológicos foi de 59% (IC de 95%: 23 a 78%) para os menores de 4 anos e de 78% (IC de 95%: 54 a 90%) para as crianças de 4 a 7 anos. Com os casos confirmados como causados por sorogrupo B, as eficácias estimadas foram maiores, mas se ampliaram os intervalos de confiança. O efeito protetor da vacina em relação à mortalidade em crianças menores de 4 anos foi estimado em 76% (IC 95%: 41 a 91%). Outros dados apresentados sugerem que as mais baixas eficácias encontradas, quando se analisam os menores de 4 anos, decorrem da seletividade da confirmação diagnóstica que exclui os casos mais graves que morrem a poucas horas do início dos sintomas, associada à modificação do curso da doença (atenuação) em vacinados. Por isso, indica-se a vacinação, inclusive em menores de 4 anos, nas situações epidêmicas. Results of the evaluation of the anti-meningococcal BC Cuban vaccine based on routine epidemiological surveillance information of meningitis for the years 1990 to 1992, following mass-vaccination of 232,022 children aged between 3 months and 7 years in 1989/90 during an epidemic of serogroup B meningococcal disease in the State of Santa Catarina, Brazil, are presented. The protective efficacy of the vaccine was calculated from the incidence rates for the cohort of vaccinated and non-vaccinated children in 20 municipalities. Main results for cases confirmed by bacteriological tests were 59% (CI 95%: 23 to 78%) for children aged under 4 years and 78% (CI 95%: 54 to 90%) for children aged 4 to 7 years. Eighty-six percent of cases serogrouped (n=29) were B, and in these cases efficacy increased to 66% (<4 years) and 88% (4-7 years), but at 95% CI were wider. The protective efficacy based on death rates from the disease in children <4 years was 76% (CI 95%: 41 to 91%). There was no evidence of decreasing protective efficacy in the three year follow-up, as shown by the yearly An interesting hypothesis arising from the findings is that the lower protective efficacy for children aged <4 years, observed in studies in which only cases confirmed by laboratory tests are analysed, could be due to a selective effect of this procedure. More severe cases die shortly after the onset of the disease, often before medical care is provided. On the other hand, the attenuation of the disease by vaccination gives a better chance for medical intervention and collection of samples for laboratory analysis. Finally, the authors support the use of the vaccine in epidemics of serogroup B meningococcal disease. estimates. They also suggest that three, rather than two doses of vaccine should be tested in children under 2 years of age to further increase its efficacy.